Perilaku Halal Lifestyle dalam Meningkatkan Minat terhadap Pembelian Produk Halal - Azizah, Nurazizah; Aprilia, Nila; Ismail, Asep Syarif; Marlina, Lina (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
This study aims to describe the halal lifestyle behavior and purchasing intention in halal products among students of the Sharia Economics Study Program at Universitas Siliwangi. The research employs a descriptive statistical approach with primary data collection techniques complemented by a literature review. The findings of this research indicate that a halal lifestyle can enhance purchasing intention in halal products, as it has become a necessity for Muslims. Based on this study, it is evident that 95% of the sampled students from the Sharia Economics Study Program at Universitas Siliwangi have adopted a halal lifestyle. Consequently, this will increase the students' intention in purchasing halal products.